Population Dynamics of Acromyrmex crassispinus (Forel) (Hymenoptera: Formicidae) and Attacks on Pinus taeda Linnaeus (Pinaceae) plantations - Mariane Aparecida Nickele; Wilson Reis Filho (Sociobiology, 2015)
This work aimed to study the population dynamics of Acromyrmex crassispinus (Forel) in Pinus taeda L. plantations, evaluating the density and spatial distribution of nests over time, inferring about the period of the first nuptial flight of A. crassispinus colonies, and evaluating the levels of attack of this leaf-cutting ant on P. taeda plants. Assessments were performed monthly in the first year after planting, every three months until the third year and every six months until the plantation was six years old. The presence of nests was observed only after 15 months after planting. The nest density gradually increased until the planting completed 30 months, and decreased when the forest canopy began to close (after 54 months). Spatial distribution of A. crassispinus nests was random. Probably, the first nuptial flight of an A. crassispinus colony occurs after the third year of the colony foundation. Pinus taeda plants were not attacked by A. crassispinus throughout the evaluation period. Then, when dealing with a replanting area of Pinus plantation, where the previous forest has not been subject to pruning nor thinning, the problem with A. crassispinus is almost null if the clearcutting and the new planting occur during the winter. In this case, leaf-cutting ants control can be alleviated and it is not necessary to carry out systematic control of ants where A. crassispinus is the predominant leaf cutting ant species. Acromyrmex crassispinus control should be done only if nests are located or if attacked plants by ants are detected.